Developmental behavioral genetics research on school achievement is missing vulnerable children, to our detriment. Issue 183 (26th September 2022) - Holden, LaTasha R.; Haughbrook, Rasheda; Hart, Sara A.
Abstract: Gene–environment processes tell us how genetic predispositions and environments work together to influence children in schools. One type of gene–environment process that has been extensively studied using behavioral genetics methods is a gene‐by‐environment interaction. A gene‐by‐environment interaction shows us when the effect of your context on a phenotype differs depending on your genetic predispositions, or vice versa, when the effect of your genetic predispositions on a phenotype differs depending on your context. Developmental behavioral geneticists interested in children's school achievement have examined many different contexts within the gene‐by‐environment interaction model, including contexts measured from within children's home and school environments. However, this work has been overwhelmingly focused on WEIRD samples children, leaving us with non‐inclusive scientific evidence. This can lead to detrimental outcomes when we overgeneralize this non‐inclusive scientific evidence to racialized groups. We conclude with a call to include racialized children in more research samples.